The Versatility of Serine Proteases from Brazilian Bothrops Venom: Their Roles in Snakebites and Drug Discovery - Romanazzi, Marcela [UNESP]; Filardi, Eloise T. M. [UNESP]; Pires, Geovanna M. M. [UNESP]; Cerveja, Marcos F. [UNESP]; Melo-dos-Santos, Guilherme [UNESP]; Oliveira, Isadora S.; Ferreira, Isabela G.; Cerni, Felipe A.; Santos-Filho, Norival Alves [UNESP]; Monteiro, Wuelton M.; Almeida, José R.; Vaiyapuri, Sakthivel; et al. (MDPI, 2025)
Serine proteases are multifunctional and versatile venom components found in viper snakes, including the Bothrops species, a widely distributed genus notorious for causing the highest number of snakebites across Latin America. These enzymes, representing a significant fraction of Bothrops venom proteomes, exhibit a wide range of biological activities that influence blood coagulation, fibrinolysis, and inflammation. This review provides a comprehensive overview of serine proteases, with a particular focus on those found in the venom of Brazilian Bothrops snakes. The discussion begins with a summary of snake species found in Brazil and their medical relevance. Specifically addressing the Bothrops genus, this review explores the distribution of these species across Brazilian territory and their associated medical importance. Subsequently, the article investigates the biochemistry of Bothrops venoms and the clinical manifestations induced by envenomation. Finally, it offers an in-depth discussion on the serine proteases, highlighting their biochemical properties, mechanisms of action, and potential therapeutic applications. Furthermore, this review provides an in-depth exploration of the diverse serine proteases found in Bothrops venoms and their functional significance, from thrombin-like effects to potent fibrinogenolytic actions, which determine the clinical manifestations of envenomation. This review delves into the evolutionary adaptations and biochemical diversity of serine proteases in Bothrops venoms, emphasizing their critical roles in venom functionality and the resulting pathophysiological effects. Additionally, it opens new avenues for utilizing these enzymes in biomedical applications, underscoring their potential beyond toxinology.
Keywords: coagulation; serine protease; snakebite; venom